Depiction of Women in the Selected Works of R. K. Narayan- An Analysis - Vanamala, M; Himabindu, S (Integrated Journal for Research in Arts and Humanities, 2023)
R. K. Narayan, one of the greatest Indian writers and a major contributor to English fiction, has presented the lives of women around and depicted women characters with varied facets in his fiction. Most of his works reflect the predicament of women and the social reality in which they try to assimilate themselves at times. He is a writer who could portray women depicting their psychological urges. Narayan’s works depict the role of women in family and society and show a gradual transformation in these women characters and evolve them to their best at the societal spectrum. He portrayed his women characters with all shades creating a signature effect with regard to characterization of women in society. This paper examines the various female characters – modern as well as traditional and the differences in their thought patterns, habits, ambitions, beliefs, conduct, aspirations and their way of looking at life. My research focuses on few observations on the portrayal and depiction of women in the selected works of R. K. Narayan with a view of exploring the female characters and different aspects of human nature and human life. This paper also proves the fact that apart from providing aesthetic pleasure, these selected literary texts depict the various facades of women in our everyday lives. It also portrays a paradigm shift that the female characters experience by rendering a message to the world around. This paper gives few insights into life and the predicaments which as human beings we falter on. This paper also suggests and recommends the readers to explore such texts and characters to develop an aesthetic ability and a sense of appreciation for the works of R. K. Narayan.